46, XY DSD with Female or Ambiguous External Genitalia at Birth due to Androgen Insensitivity Syndrome, 5α-Reductase-2 Deficiency, or 17β-Hydroxysteroid Dehydrogenase Deficiency: A Review of Quality of Life Outcomes. (31st August 2009) - Wisniewski, Amy B.; Mazur, Tom
Abstract : Disorders of sex development refer to a collection of congenital conditions in which atypical development of chromosomal, gonadal, or anatomic sex occurs. Studies of 46, XY DSD have focused largely on gender identity, gender role, and sexual orientation. Few studies have focused on other domains, such as physical and mental health, that may contribute to a person's quality of life. The current review focuses on information published since 1955 pertaining to psychological well-being, cognition, general health, fertility, and sexual function in people affected by androgen insensitivity syndromes, 5-α reductase-2 deficiency, or 17β -hydroxysteroid dehydrogenase-3 deficiency—reared male or female. The complete form of androgen insensitivity syndrome has been the focus of the largest number of investigations in domains other than gender. Despite this, all of the conditions included in the current review are under-studied. Realms identified for further study include psychological well-being, cognitive abilities, general health, fertility, and sexual function. Such investigations would not only improve the quality of life for those affected by DSD but may also provide information for improving physical and mental health in the general population.